Molecular diagnosis of retinoblastoma by circulating tumor DNA analysis. (September 2021) - Jiménez, Irene; Frouin, Éléonore; Chicard, Mathieu; Dehainault, Catherine; Le Gall, Jessica; Benoist, Camille; Gauthier, Arnaud; Lapouble, Eve; Houdayer, Claude; Radvanyi, François; Bernard, Virginie; Brisse, Hervé J.; et al.
Abstract: Purpose: The analysis of circulating tumor DNA (ctDNA), a fraction of total cell-free DNA (cfDNA), might be of special interest in retinoblastoma patients. Because the accessibility to tumor tissue is very limited in these patients, either for histopathological diagnosis of suspicious intraocular masses (biopsies are proscribed) or for somatic RB1 studies and genetic counseling (due to current successful conservative approaches), we aim to validate the detection of ctDNA in plasma of non-hereditary retinoblastoma patients by molecular analysis of RB1 gene. Experimental design: In a cohort of 19 intraocular unilateral non-hereditary retinoblastoma patients for whom a plasma sample was available at diagnosis, we performed high-deep next-generation sequencing (NGS) of RB1 in cfDNA. Two different bioinformatics/statistics approaches were applied depending on whether the somatic RB1 status was available or not. Results: Median plasma sample volume was 600 μL [100–1000]; median cfDNA plasma concentration was 119 [38–1980] and 27 [11–653] ng/mL at diagnosis and after complete remission, respectively. In the subgroup of patients with known somatic RB1 alterations (n = 11), seven of nine somatic mutations were detected (median allele fraction: 6.7%). In patients without identified somatic RB1 alterations (n = 8), six candidate variants were identified for seven patients. Conclusions: Despite small tumor size, blood-ocular barrier, poor ctDNA blood release and limited plasma sample volumes, we confirm that it is possible to detect ctDNA with high-deep NGS in plasma from patients with intraocular non-hereditary retinoblastoma. This may aid in diagnosis of suspicious cases, family genetic counseling or follow-up of residual intraocular disease. Highlights: Intraocular nonhereditary retinoblastoma releases circulating tumor DNA into blood. Study of circulating tumor DNA might be useful in non-hereditary retinoblastoma. Interest for the molecular diagnosis of suspicious intraocular masses. Utility for somatic RB1 studies and genetic counseling of non-enucleated cases.